Examining The Relationship Between Perceived Organisational Support and Job Crafting in Nurses - İzzet Erdem (Association of Nurse Managers, 2021)
Aim: This study was conducted to examine the effect of perceived organisational support on job crafting on nurses. Method: The research population consists of 198,103 registered nurses working in Turkey, according to the 2019 data of the Ministry of Health. The study sample consists of 505 nurses, and data were collected between 10.02.2020-22.02.2020 via Google Forms. The 'Personal Information Form, Perceived Organisational Support Scale (POSS), and Job Crafting Scale (JCS)' was used in the research. The data obtained were analysed with the SPSS 16.0 (Statistical Package for Social Science) program. The mean scores of the scales were calculated, and regression analysis was performed to determine the effect of perceived organisational support on job crafting. Results: As a result of the regression analysis, it was seen that 6% (R2=.060) of the change in the task crafting variable was explained by the perceived organisational support. There was no problem with the significance of the exploratory power of the model (F=32.117, p=.000). 10.5% (R2=.105) of the change in the cognitive crafting variable was explained by perceived organisational support, and there was no problem in terms of significance (F=58.947, p=.000). Furthermore, perceived organisational support explained 8% (R2=.80) of the change in the relational crafting variable, and the model was found to be statistically significant at a very high level (F=43.871, p=.000). Perceived organisational support depends on task crafting (β =.245, t = 29.835, p =.000), cognitive crafting (β =.324, t =28.215, p =.000), and relational crafting (β=.29.416, p=.000). These were found to have a significant and positive effect. Conclusion: It has been observed that the perceived organisational support in nurses has a significant and positive effect on job crafting dimensions.